Immunological impact of tetrahydrobiopterin on the central nervous system in a murine model of rabies virus infection - Brito, Caio Vinicius Botelho (2021)
Currently, the Milwaukee protocol presents healing results in human beings affected by the rabies virus. However, there are many points to clarify on the action of drugs and the immune mechanism involved in the evolution of the disease. One of the drugs used is biopterin, which is an important cofactor for nitric oxide, important for preventing vasospasm. Thus, we describe the effect of biopterin on some inflammatory factors in a rabies virus infection developed in an animal model. The immunological mediators studied in animals infected with rabies virus submitted to doses of sapropterin were Anti-RABV, IL-6, IL-2, IL-17a, INF-gamma and Anti-iNOS. It is suggested that the medication in the context of a RABV infection already installed, had the effect of modulating the inflammatory mechanisms mainly linked to the permeability of the blood-brain barrier and the migration of cytotoxic cells.